Konteks dalam Studi Linguistik Pragmatik - Akhmad Saifudin (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2018)
This paper tries to provide an understanding of the context in pragmatic linguistic studies. Pragmatic linguistic studies are known as branches of linguistics which discuss the meaning of speech based on context. In this paper the context is understood as a conceptual framework about everything that is used as a reference in speaking or understanding speech. Context is classified into two types, namely linguistic and nonlinguistic. Linguistic contexts are contexts whose references are contained in previous speeches and nonlinguistic contexts are not found in speech or outside of language. The nonlinguistic context can be divided into four types, namely physical, psychological, social, and shared knowledge contexts.Keywords: Pragmatics, Context, Text, Meaning,Â Shared knowledge